J. García Pérez, J. J. Bacallado Aránega, R. García Becerra, I. Santos Perdomo, C. Ruiz Carreira & A. Delgado Izquierdo Mariposas diurnas de Canarias - Antonio Vives Moreno (SHILAP, 2025)
Revisión de publicaciones